Annotated bird sighting list for spring 1998 compiled by Fred Lesher - Lesher, Fredet al (1998)
An annotated list of birds sighted by Fred Lesher. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1998. Epson - sheet feed/flatbed